Bifurcation of the Kirkendall marker plane and the role of Ni and other impurities on the growth of Kirkendall voids in the Cu–Sn system. (1st June 2017) - Baheti, Varun A.; Kashyap, Sanjay; Kumar, Praveen; Chattopadhyay, Kamanio; Paul, Aloke
Abstract: The presence of bifurcation of the Kirkendall marker plane, a very special phenomenon discovered recently, is found in a technologically important Cu–Sn system. It was predicted based on estimated diffusion coefficients; however, could not be detected following the conventional inert marker experiments. As reported in this study, we could detect the locations of these planes based on the microstructural features examined in SEM and TEM. This strengthens the concept of the physico–chemical approach that relates microstructural evolution with the diffusion rates of components and imparts finer understanding of the growth mechanism of phases. The estimated diffusion coefficients at the Kirkendall marker planes indicates that the reason for the growth of the Kirkendall voids is the non–consumption of excess vacancies which are generated due to unequal diffusion rate of components. Systematic experiments using different purity of Cu in this study indicates the importance of the presence of impurities on the growth of voids, which increases drastically for ≥ 0.1 wt% impurity. The growth of voids increases drastically for electroplated Cu, commercially pure Cu and Cu(0.5 at.% Ni) indicating the adverse role of both inorganic and organic impurities. Void size and number distribution analysis indicates the nucleation of new voids along with the growth of existing voids with the increase in annealing time. The newly found location of the Kirkendall marker plane in the Cu3 Sn phase indicates that voids grow on both the sides of this plane which was not considered earlier for developing theoretical models. Graphical abstract: Image